Solamen Vaillanti Mollusk powder as an efficient biosorbent for removing cobalt ions from aqueous solution: Kinetic and equilibrium studies - Barboza Arenas, Luis Andrés (2022)
In this research, Solamen Vaillanti mollusk (SVM) skin biosorbent was synthesized and used as a low-cost and environmentally friendly adsorbent to eliminate cobalt (Co2+) heavy metal ion from aqueous solution. The surface morphology and specific surface area of SVM were analyzed by SEM and BET analyses. Also, the impact of various effective factors like pH, temperature, contact time, biosorbent dose, and cobalt ion concentration was studied on the uptake process. According to our study, the highest biosorption efficiency of Co2+ (97.31%) was attained at pH 5, a mixing speed of 200 rpm, Co2+ ion concentration of 5 mg l-1, and biosorbent dosage of 2 g l-1 after 50 min. Also, the maximum biosorption capacity of SVM biosorbent was 16.23 mg l-1, which was achieved at pH 5 and temperature of 25 °C. Moreover, kinetic and equilibrium studies demonstrated that the quasi-second-order kinetic model and the Langmuir isotherm model are better compatible with the experimental data. Furthermore, the reusability of the bioadsorbent showed that it can be reused in 4 cycles in the bioadsorption process.